Trump's "Travel Ban": how the discourse of two executive orders conceals animus against Muslims - Fredrickson, Amy, author; Cloud, Doug, advisor; Jacobi, Tobi, committee member; Prasch, Allison, committee member (Colorado State University. Libraries, 2018)
The implementation, although temporary, of the Trump administration's "travel ban" executive orders sparked public criticism. Many criticized these orders for restricting travel based on religious profiling, an inimical sentiment seemingly contradicting the "core American values" of acceptance, tolerance, and equality. While many criticized these orders thus, few have closely analyzed the discourse of the source material itself, nor considered how these orders compliment and contradict previous presidential rhetoric on immigration. Consequently, this research positions the Trump administration's executive orders within the context of previous presidential administrations, considers why the Trump administration might attempt to conceal animus against Muslims within the context of a democratic, liberal system, and, by the method of critical discourse analysis, outlines three discursive features the administration used to obfuscate prejudice against Muslims. The research reaches the conclusion that the Trump administration did, in fact, discursively conceal animus against Muslims throughout its "travel ban" executive orders and their surrounding discourse, subsequently highlighting not only the Trump administration's concealed discrimination, but the manipulative and coercive ability of presidential rhetoric.